Cybersecurity and Customer Satisfaction in the Age of Digital Banking: An Application of Information Systems Success Model - Ologun, Victor; Yusuf, Isaac; Obioha, Chiamaka; Akande, Jamiu; Ameen, Abdulrazaq; John, Stephen (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
In the rapidly evolving digital banking environment, cybersecurity has emerged as a critical factor influencing customer trust, system usage, and overall satisfaction. However, emergence of cybersecurity has also led to a parallel rise in cyberthreats involving data breaches, online fraud, phishing attacks, and other cybercrimes. This study integrated cybersecurity system within the Information Systems Success Model (ISSM) to explore how it affects customer satisfaction as the Nigeria’s banking industry goes digital. Using quantitative research approach, data were collected through structured questionnaires administered 310 respondents including bank customers, employees and IT managers. Ordered Logistic Regression (OLR) model was employed to test the predictive power of each explanatory variable. The findings reveal that information quality (β = 0.019, p < 0.05), service quality (β = 0.047, p < 0.05), use (β = 0.046, p < 0.05), and user satisfaction (β = 0.205, p < 0.05) have positive and significant effects on customer satisfaction, while system quality (β = -0.178, p > 0.05) and net benefits (β = 0.125, p > 0.05) show insignificant effects. This study concluded that the information systems success model is applicable to the Nigeria’s banking industry as cybersecurity system affects customer satisfaction. Therefore, the study recommended that customers should offer feedback on their experiences with the bank’s services, particularly regarding cybersecurity system effectiveness; and bank managers should invest in maintaining reliable and secure cybersecurity system, involving high uptime, smooth system performance, high-quality customer support and resilience against cyber threats.